The role of hepatic transferrin receptor 2 in the regulation of iron homeostasis in the body - Worthen, Christal A.; Enns, Caroline A. (Frontiers in Pharmacology, 2014)
Fine tuning of body iron is required to prevent diseases such as iron-overload and anemia. The putative iron-sensor, transferrin receptor 2 (TfR2), is expressed in the liver and mutations in this protein result in the iron-overload disease Type III hereditary hemochromatosis (HH). With the loss of functional TfR2, the liver produces about two-fold less of the peptide hormone hepcidin, which is responsible for negatively regulating iron uptake from the diet. This reduction in hepcidin expression leads to the slow accumulation of iron in the liver, heart, joints, and pancreas and subsequent cirrhosis, heart disease, arthritis, and diabetes. TfR2 can bind iron-loaded transferrin in the bloodstream, and hepatocytes treated with transferrin respond with a two-fold increase in hepcidin expression through stimulation of the BMP-signaling pathway. Loss of functional TfR2 or its binding partner, the original HH protein (HFE), results in a loss of this transferrin-sensitivity. While much is known about the trafficking and regulation of TfR2, the mechanism of its transferrin-sensitivity through the BMP-signaling pathway is still not known.